2018
DOI: 10.12657/denbio.080.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thinning on Pinus pinea L. development and physico-chemical soil characteristics in northwestern Tunisia: modeling of radial growth under thinning intensity

Abstract: In this study, the potential beneficial impacts that the thinnings intensity on stand behavior and soil properties are also studied. This study was designed to test the hypothesis that thinning to various stand densities at young age enhance productivity of wood, cones and the physicochemical characteristics of the soil in Pinus pinea stands. We based our study on four thinning intensity (30, 40, 50 and 65%) in comparison with the control plot. The study was supplemented by a haracterization of radial growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Cherubini (1993) concluded that precipitation plays the most important role in tree-ring growth in Pinus pinea L. Calama et al (2019) detected a positive relationship between rainfall and growth, extending back to the precipitation of previous autumn and winter seasons. Similar findings have been reported in previous studies on dendroecological growth-climate relationships for the species (Mazza et al 2014, Natalini et al 2015, 2016, Jaouadi et al 2018. Total rainfall occurring during the period from October of the previous year to September of the current growth year as well as mean temperature in May and June, are the main climatic factors driving secondary growth in Pinus pinea (Calama et al 2019).…”
Section: Precipitation Effectssupporting
confidence: 90%
“…Cherubini (1993) concluded that precipitation plays the most important role in tree-ring growth in Pinus pinea L. Calama et al (2019) detected a positive relationship between rainfall and growth, extending back to the precipitation of previous autumn and winter seasons. Similar findings have been reported in previous studies on dendroecological growth-climate relationships for the species (Mazza et al 2014, Natalini et al 2015, 2016, Jaouadi et al 2018. Total rainfall occurring during the period from October of the previous year to September of the current growth year as well as mean temperature in May and June, are the main climatic factors driving secondary growth in Pinus pinea (Calama et al 2019).…”
Section: Precipitation Effectssupporting
confidence: 90%
“…Tree growth has been known to be sensitive to rainfall (Grogan, Schulze 2012;Bauwe et al 2015;Natalini et al 2015), air temperature (Schweingruber 1996; Jump et al 2006;Savva et al 2006;Natalini et al 2015), wind (Urban et al 1994), solar cycles (Rigozo et al 2002;Šimůnek et al 2020) and air pollution (Putalová et al 2019;Mikulenka et al 2020;Sidor et al 2021). Similarly, the radial growth of trees could also be affected by biotic factors, such as game damage (Cukor et al 2019;Vacek et al 2020), silvicultural treatments (Pérez- de-Lis et al 2011;Remeš et al 2015;Jaouadi et al 2018) or fertilization (Ponton et al 2019;Vacek et al 2019;Gallo et al 2021). However, these variables impact species differently and the same species at different habitat (Dié et al 2015) depending on their environment.…”
mentioning
confidence: 99%